Capital, labor, and gender: The consequences of large-scale land transactions on household labor allocation - Hajjar, Reem; Ayana, Alemayehu N.; Rutt, Rebecca; Hinde, Omer; Liao, C.; Keene, Stephanie; Bandiaky-Badji, Solange; Agrawal, Arun (Journal of Peasant Studies, 2020)
Contemporary large-scale land transactions (LSLTs), also called land grabs, are historically unprecedented in their scale and pace. They have provoked robust scholarly debates, yet studies of their gender-differentiated impacts remain more rare, particularly when it comes to how changes in control over land and resources affect women's labor, and thereby their livelihoods and well-being. Our comparative study of four LSLTs in western Ethiopia finds that the transactions led to substantial land use change, including relocation and decrease in size of smallholder parcels, loss of communally-held grazing lands, and loss of forests. These changes had far-reaching impacts on household labor allocation, the gendered division of labor, and household wellbeing. But their effects on women are both more adverse and more severe, expressed in terms of increased wage labor to make up for lost land and livestock, more time spent gathering firewood and water from increasingly distant locations, and an increased intensity of household responsibilities where male members underwent wage labor migration. These burdens led to negative psychological, corporal, and material effects on women living in and near transacted areas compared to their situation prior to transactions. This article both responds to the deficit in studies on the impacts of LSLTs on gendered livelihoods, labor relations, and wellbeing outcomes, and lays the groundwork for future research. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; afrique; agriculture; approches et analyses; environnement; inégalités; inégalités hommes-femmes; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; éthiopie